English grammar simplified - Fernald, James Champlin, 1838-1918 (Funk & Wagnalls Company, Inc., 1963)
A summary of practical English grammar. Defines the various parts of the language and explains how they should be used to make an effective sentence. Includes sections on puctuation and mechanics.